Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's find the first derivative.
Using quotient rule
[tex]f(x)=\frac{g(x)}{h(x)}[/tex]
[tex]f'(x)=\frac{g'(x)*h(x)-g(x)*h'(x)}{h^2(x)}[/tex]
then:
[tex]y=\frac{x+2}{x-3}[/tex]
[tex]f(x)=y[/tex]
[tex]g(x)=x+2[/tex]
[tex]g'(x)=1[/tex]
[tex]h(x)=x-3[/tex]
[tex]h'(x)=1[/tex]
Let's replace
[tex]f'(x)=\frac{g'(x)*h(x)-g(x)*h'(x)}{h^2(x)}[/tex]
[tex]y'=\frac{1*(x-3)-(x+2)*1}{(x-3)^2}[/tex]
[tex]y'=\frac{x-3-x-2}{(x-3)^2}[/tex]
[tex]\boxed{y'=\frac{-5}{(x-3)^2}}[/tex]
the second derivative is the derivative of our first derivative.
[tex]y'=\frac{-5}{(x-3)^2}[/tex]
We can write this function as
[tex]y'=-5*(x-3)^{-2}[/tex]
now we have to use the Chain rule's
[tex]f(u)=-5u^{-2}[/tex]
and
[tex]g(x)=x-3[/tex]
[tex]f[g(x)]=-5*(x-3)^{-2}[/tex]
then
[tex]f'[g(x)]=f'(u)*g'(x)[/tex]
[tex]f'(u)=-5*(-2)*u^{-3}=10*u^{-3}[/tex]
[tex]g'(x)=1[/tex]
[tex]f'[g(x)]=f'(u)*g'(x)[/tex]
Let's replace
[tex]f'[g(x)]=10*u^{-3}*1[/tex]
Let's change u by [tex](x-3)[/tex]
[tex]f'[g(x)]=10*u^{-3}[/tex]
[tex]f'[g(x)]=10*(x-3)^{-3}[/tex]
[tex]\boxed{\boxed{y''=\frac{10}{(x-3)^{3}}}}[/tex]
Using quotient rule
[tex]f(x)=\frac{g(x)}{h(x)}[/tex]
[tex]f'(x)=\frac{g'(x)*h(x)-g(x)*h'(x)}{h^2(x)}[/tex]
then:
[tex]y=\frac{x+2}{x-3}[/tex]
[tex]f(x)=y[/tex]
[tex]g(x)=x+2[/tex]
[tex]g'(x)=1[/tex]
[tex]h(x)=x-3[/tex]
[tex]h'(x)=1[/tex]
Let's replace
[tex]f'(x)=\frac{g'(x)*h(x)-g(x)*h'(x)}{h^2(x)}[/tex]
[tex]y'=\frac{1*(x-3)-(x+2)*1}{(x-3)^2}[/tex]
[tex]y'=\frac{x-3-x-2}{(x-3)^2}[/tex]
[tex]\boxed{y'=\frac{-5}{(x-3)^2}}[/tex]
the second derivative is the derivative of our first derivative.
[tex]y'=\frac{-5}{(x-3)^2}[/tex]
We can write this function as
[tex]y'=-5*(x-3)^{-2}[/tex]
now we have to use the Chain rule's
[tex]f(u)=-5u^{-2}[/tex]
and
[tex]g(x)=x-3[/tex]
[tex]f[g(x)]=-5*(x-3)^{-2}[/tex]
then
[tex]f'[g(x)]=f'(u)*g'(x)[/tex]
[tex]f'(u)=-5*(-2)*u^{-3}=10*u^{-3}[/tex]
[tex]g'(x)=1[/tex]
[tex]f'[g(x)]=f'(u)*g'(x)[/tex]
Let's replace
[tex]f'[g(x)]=10*u^{-3}*1[/tex]
Let's change u by [tex](x-3)[/tex]
[tex]f'[g(x)]=10*u^{-3}[/tex]
[tex]f'[g(x)]=10*(x-3)^{-3}[/tex]
[tex]\boxed{\boxed{y''=\frac{10}{(x-3)^{3}}}}[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.